Perceived Ethnic Discrimination and Depressive Symptoms Among Biethnic Adolescents in South Korea - Gum Ryeong Park; Inseo Son; Seung-Sup Kim (Korean Society for Preventive Medicine, 2016)
Objectives This study investigated the association between perceived ethnic discrimination and depressive symptoms among biethnic adolescents in South Korea. Methods We performed a cross-sectional study of 4141 biethnic adolescents using data from the 2012 National Survey of Multicultural Families. Perceived ethnic discrimination was measured using the question "Have you ever been discriminated against or ignored because either of your parents is not a Korean?" with an assessment of depressive symptoms over the past 12 months. Logistic regression was applied to examine potential associations between perceived ethnic discrimination and depressive symptoms. Results Among 4141 biethnic adolescents, 558 (13.5%) reported having experienced ethnic discrimination. The most common discriminatory perpetrators were friends (n=241, 5.8%), followed by strangers (n=67, 1.6%). Depressive symptoms were related to experience of ethnic discrimination (odds ratio [OR], 3.80; 95% confidence interval [CI], 2.89 to 4.98) after adjusting for potential confounders. In an analysis focusing on the perpetrators of discrimination, depressive symptoms were found to be associated with perceived ethnic discrimination from friends (OR, 3.95; 95% CI, 2.75 to 5.68), teachers (OR, 4.53; 95% CI, 2.16 to 9.51), family members and relatives (OR, 3.89; 95% CI, 1.59 to 9.48), neighbors (OR, 2.48; 95% CI, 1.14 to 5.38), and strangers (OR, 2.49; 95% CI, 1.30 to 4.79). Furthermore, the OR for depressive symptoms among those exposed to 1, 2, or 3 or more discriminatory perpetrators were 3.61 (95% CI, 2.49 to 5.24), 3.61 (95% CI, 1.68 to 7.74), and 6.69 (95% CI, 2.94 to 15.22), respectively. Conclusions According to our findings, friends were the most common perpetrators of discrimination and the experience of ethnic discrimination was associated with depressive symptoms among biethnic adolescents in South Korea.